Ozone Reacts With Carbon Black to Produce a Fulvic Acid-Like Substance and Increase an Inflammatory Effect. (October 2020) - Ghio, Andrew J.; Gonzalez, David H.; Paulson, Suzanne E.; Soukup, Joleen M.; Dailey, Lisa A.; Madden, Michael C.; Mahler, Beth; Elmore, Susan A.; Schladweiler, Mette C.; Kodavanti, Urmila P.
Exposure to ambient ozone has been associated with increased human mortality. Ozone exposure can introduce oxygen-containing functional groups in particulate matter (PM) effecting a greater capacity of the particle for metal complexation and inflammatory effect. We tested the postulate that (1) a fulvic acid-like substance can be produced through a reaction of a carbonaceous particle with high concentrations of ozone and (2) such a fulvic acid-like substance included in the PM can initiate inflammatory effects following exposure of respiratory epithelial (BEAS-2B) cells and an animal model (male Wistar Kyoto rats). Carbon black (CB) was exposed for 72 hours to either filtered air (CB-Air) or approximately 100 ppm ozone (CB-O3 ). Carbon black exposure to high levels of ozone produced water-soluble, fluorescent organic material. Iron import by BEAS-2B cells at 4 and 24 hours was not induced by incubations with CB-Air but was increased following coexposures of CB-O3 with ferric ammonium citrate. In contrast to CB-Air, exposure of BEAS-2B cells and rats to CB-O3 for 24 hours increased expression of pro-inflammatory cytokines and lung injury, respectively. It is concluded that inflammatory effects of carbonaceous particles on cells can potentially result from (1) an inclusion of a fulvic acid-like substance after reaction with ozone and (2) changes in iron homeostasis following such exposure.